Exploring the nutritional and biological properties of green coffee extracts: A comparative study of aqueous and enzymatic extraction processes - Flávia Souza Almeida; Fernanda Furlan Goncalves Dias; Matthew William Ford; Stanislau Bogusz Junior; Ana Carla Kawazoe Sato; Juliana Maria Leite Nobrega de Moura Bell (Current Research in Food Science)
The effects of aqueous (AEP) and enzyme-assisted aqueous extraction processes (EAEP) on the biological and nutritional properties of green coffee extracts (protein and antioxidant-rich fraction) were investigated. All extracts exhibited high in vitro protein digestibility (>98%), regardless of the pH and use of enzymes during extraction, probably due to the low molecular weight of coffee proteins. Raising extraction pH from 7.0 to 9.0 resulted in extracts with lower concentrations of caffeine and some phenolic compounds such as chlorogenic and cinnamic acids, as well as catechin and epicatechin. This led to a reduction in the antioxidant activity of the extracts obtained at alkaline pH (AEP – pH 9.0). Overall, higher phenolic and caffeine extractability was achieved at neutral pH (AEP – pH 7.0), with no observed improvement in extraction yields when carbohydrases and/or proteases were employed. Coffee extracts generated by AEP at pH 7.0 exhibited the highest lipase inhibitory activity (66%), primarily attributed to their higher chlorogenic acid concentration. Conversely, EAEP extracts exhibited higher angiotensin-converting enzyme inhibition (up to 85%) compared to AEP extracts (68.5–74.3%). This strong inhibitory activity is likely related to the presence of both phenolic compounds (mainly chlorogenic acid) and smaller peptides. Nevertheless, all extracts exhibited low effectiveness for α-glucosidase inhibition (≤14%) and antimicrobial activity against S. aureus and E. coli. The current research underscores the feasibility of modulating the composition of green coffee extracts using sustainable and scalable AEP and EAEP, paving the way for developing tailored extracts with specific biological properties.